172k views
0 votes
9) f(n)=-n-1 g(n)=-4n-4 Find (f .g)(n)

User Giantriant
by
5.2k points

1 Answer

4 votes

Answer:


\begin{gathered} (f.g)(n)=4(n+1)^2\text{ } \\ OR \\ 4n^2+8n+4 \end{gathered}

Step-by-step explanation:

Given the functions:


\begin{gathered} f(n)=-n-1 \\ g(n)=-4n-4 \\ \\ We\text{ want to find} \\ (f.g)(n) \end{gathered}

This, we only need to multiply the two given functions because:


\begin{gathered} (f.g)(n)=f(n)g(n) \\ \\ =(-n-1)(-4n-4) \\ =-(n+1).(-4)(n+1) \\ =4(n+1)(n+1) \\ =4(n+1)^2 \\ OR \\ 4(n^2+2n+1) \\ =4n^2+8n+4 \end{gathered}

User Chanioxaris
by
5.0k points